Situated cognition and the study of culture: an introduction - Morgan, B (Duke University Press, 2017)
The article surveys three major positions in early debates about situated cognition in the 1990s as they are represented in particular in the work of Edwin Hutchins, Jean Lave, Etienne Wenger, Tim van Gelder, Andy Clark, Jerome Bruner and John Haugeland. Rather than arbitrate among the three positions and declare a winner, the article suggests that the very tensions between sub-personal, supra-personal and personal levels of analysis evident in the debates are a necessary feature of the study of situated cognition, which can be resolved only by the sort of case by case negotiation of which we find records in the cultural archive. The eight case studies collected in this special issue can be read as explorations of the historical variety of these lived negotiations.